PENINGKATAN MOTIVASI DAN KETERAMPILAN MENULIS NARASI MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) SISWA KELAS X JASA BOGA 2 SMK NEGERI 3 SAMARINDA TAHUN PEMBELAJARAN 2016/2017 - NFN Slamet (Kantor Bahasa Kalimantan Timur, 2017)
This research was a classroom action research. The data collection included observation, interviews, tests, document analysis, and questionnaires. The validity of the data was measured using triangulation of the data sources and data collection methods. It was quantitative and qualitative research which applied descriptive statistical and descriptive comparative techniques. The results revealed that learning process using think pair share (TPS) cooperative learning model improved students’ motivation and skill to write narrative texts. From the first cycle, students’ motivation to write narrative texts reached 70. The second cycle reached 78%. And, the third cycle reached 90%. In pre-action, 8 students (25%) reached the mastery standard. Nineteen students (63%) succeeded in cycle I, 21 students (70%) succeeded in cycle II, and 23 students (77%) succeeded in cycle III. The average score of students' narrative text writing skills on pre-action was 64, on cycle I was 66, on cycle II was 71, and on cycle III was 76.